Suppression of Tumorigenesis: Modulation of Inflammatory Cytokines by Oral Administration of Microencapsulated Probiotic Yogurt Formulation - Aleksandra Malgorzata Urbanska; Arghya Paul; Jasmine Bhahena; Satya Prakash (Hindawi Limited, 2010)
The objective of this study was to examine the ability of a novel microencapsulated probiotic yogurt formulation to suppress the intestinal inflammation. We assessed its anticancer activity by screening interleukin-1, 6, and 12 (IL-1, 6, 12), secretory levels of tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), prostaglandin E2  (PGE2), and thromboxane B2 in the digesta obtained from the duodenum, jejunum, proximal, and distal segments of the ileum of C57BL/6J-ApcMin/J mice. Formulation-receiving animals showed consistently lower proinflammatory cytokines' levels when compared to control group animals receiving empty alginate-poly-L-lysine-alginate (APA) microcapsules suspended in saline. The concentrations of IL-12 found in serum in control and treatment group animals were significant: 46.58±16.96 pg/mL and 158.58±28.56 pg/mL for control and treatment animals, respectively. We determined a significant change in plasma C-reactive protein: 81.04±23.73 ng/mL in control group and 64.21±16.64 ng/mL in treatment group. Western blots showed a 71% downregulation of cyclooxygenase-2 (COX-2) protein in treatment group animals compared to control. These results point to the possibility of using this yogurt formulation in anticancer therapies, in addition to chronic gut diseases such as Crohn's disease, irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD) thanks to its inflammation lowering properties.